Update on Modern Management of Pheochromocytoma and Paraganglioma - Jacques W. M. Lenders; Graeme Eisenhofer (Endocrinology and Metabolism, 2017)
Despite all technical progress in modern diagnostic methods and treatment modalities of pheochromocytoma/paraganglioma, early consideration of the presence of these tumors remains the pivotal link towards the best possible outcome for patients. A timely diagnosis and proper treatment can prevent the wide variety of potentially catastrophic cardiovascular complications. Modern biochemical testing should include tests that offer the best available diagnostic performance, measurements of metanephrines and 3-methoxytyramine in plasma or urine. To minimize false-positive test results particular attention should be paid to pre-analytical sampling conditions. In addition to anatomical imaging by computed tomography (CT) or magnetic resonance imaging, new promising functional imaging modalities of photon emission tomography/CT using with somatostatin analogues such as 68Ga-DOTATATE (68Ga-labeled DOTA(0)-Tyr(3)-octreotide) will probably replace 123I-MIBG (iodine-123-metaiodobenzylguanidine) in the near future. As nearly half of all pheochromocytoma patients harbor a mutation in one of the 14 tumor susceptibility genes, genetic testing and counseling should at least be considered in all patients with a proven tumor. Post-surgical annual follow-up of patients by measurements of plasma or urinary metanephrines should last for at least 10 years for timely detection of recurrent or metastatic disease. Patients with a high risk for recurrence or metastatic disease (paraganglioma, young age, multiple or large tumors, genetic background) should be followed up lifelong.